Use of Digital Technology in Education at The State Institut of Christiany Palangka Raya - Urbanus, Urbanus (Journal of Learning and Technology, 2024)
This research explores the use of digital technology in education at the Palangka Raya State Christian Institute. The main focus of the research is to determine the impact of digital technology on learning quality, material accessibility, student engagement, and the technical challenges faced. The research method used is a qualitative approach through observation and interviews with lecturers and students as well as secondary data analysis. The results of this research show that digital technology has significantly increased the interaction between lecturers and students, enabled more flexible access to learning materials, and increased student engagement through interactive features. The conclusion of this research is that the use of digital technology in education is its ability to provide access to various educational resources. This not only broadens students' knowledge but also encourages independent learning. This research also provides recommendations for a deeper integration of technology in the curriculum and the development of digital competencies for lecturers and students. So that digital technology can continue to improve the quality of education at the Palangka Raya State Christian Religion Institute.